Legitimacy of work tasks, psychosocial work environment, and time utilization among primary care staff in Sweden - Eva Anskär; Malou Lindberg; Magnus Falk; Agneta Andersson (Taylor & Francis Group, 2019)
Objective: Primary care staff faces a complex work environment including a heavy administrative work load and perceive some work tasks as illegitimate. This study aimed to elucidate associations between the perceived legitimacy of work tasks, the psychosocial work environment, and the utilization of work time among Swedish primary care staff. Design and setting: The study was designed as a multicenter study involving all staff categories, i.e. registered nurses, primary care physicians, care administrators, nurse assistants and allied professionals, at eleven primary care centers in Sweden. Subjects: Participants completed the Bern Illegitimate Tasks Scale and the Copenhagen Psychosocial Questionnaire. They also recorded time spent on all work tasks, day by day during two separate weeks. Main outcome measures and results: More than a quarter (27%) of primary care physicians perceived a high proportion of unnecessary work tasks. After adjusting for profession, age and gender, the perception of having to perform unreasonable work tasks was positively associated with experiencing role conflicts and with the proportion of organization-related administration and service work tasks. Conclusion: Across all staff groups, the perception of unreasonable work tasks was more pronounced among staff with a high proportion of non-patient related administration. Also, the perception of having to perform a large amount of illegitimate work tasks affected the psychosocial work environment negatively, which might influence staffs perception of their professional roles. These results illuminate the importance of decision makers to thoroughly consider the distribution and allocation of non-patient related work tasks among staff in primary care.Key points We observed an interaction between perception of having a large proportion of illegitimate work tasks and impaired psychosocial work environment. • More than a quarter of the primary care physicians perceived a high proportion of unnecessary work tasks. • Across all staff groups, performing unreasonable work tasks was associated with an experience of having role conflicts. • Across all staff groups, a perception of performing unreasonable work tasks was associated with the proportion of non-patient related administrative work tasks.